2016
DOI: 10.1007/s10384-016-0427-3
|View full text |Cite
|
Sign up to set email alerts
|

Rate of progression of total, upper, and lower visual field defects in patients with open-angle glaucoma and high myopia

Abstract: The rate of progression of total, upper, and lower visual field defects was similar among patients with HM and NHM. Although HM is a risk factor for the onset of glaucoma, HM may not be a risk factor for progression of visual field defects as assessed by the progression rate under treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While the rate of VF loss in POAG eyes, [41][42][43][44][45][46][47][48][49][50][51][52] as well as differences between the patterns of VF loss in POAG and PACG eyes, 27,30,34,53 has been reported previously, this is, to our knowledge, the first study directly investigating the differences in the rate of VF loss as well as the superior-inferior asymmetry between POAG and PACG eyes with automated perimetry. Lee and colleauges compared the rate of VF loss using the Goldmann perimetry; however, their relatively small number of eyes (25 POAG eyes and 23 PACG eyes) makes the comparison challenging.…”
Section: Discussionmentioning
confidence: 48%
“…While the rate of VF loss in POAG eyes, [41][42][43][44][45][46][47][48][49][50][51][52] as well as differences between the patterns of VF loss in POAG and PACG eyes, 27,30,34,53 has been reported previously, this is, to our knowledge, the first study directly investigating the differences in the rate of VF loss as well as the superior-inferior asymmetry between POAG and PACG eyes with automated perimetry. Lee and colleauges compared the rate of VF loss using the Goldmann perimetry; however, their relatively small number of eyes (25 POAG eyes and 23 PACG eyes) makes the comparison challenging.…”
Section: Discussionmentioning
confidence: 48%
“…[87][88][89] However, the other four studies did not report an association. [90][91][92][93] Whether progressive OAG is an important cause of myopic visual morbidity therefore remains questionable. Lack of data hampered investigation of the association between myopia and VA in OAG patients.…”
Section: The Risk Of Cataract Extraction (Ce)mentioning
confidence: 99%
“…Recently, a large number of longitudinal cohort studies have shown that myopia is not a risk factor for the progression of POAG [26,[32][33][34], and the relevant results even indicated that myopia may be a protective factor for POAG progression [33]. The lamina cribrosa defect may play a role in myopia-related POAG [35,36].…”
Section: Introductionmentioning
confidence: 99%